Patterns of drug abuse among drug users with regular and irregular attendance for treatment as detected by comprehensive UHPLC‐HR‐TOF‐MS. Issue 1 (28th May 2015) - Sundström, Mira; Pelander, Anna; Simojoki, Kaarlo; Ojanperä, Ilkka
Abstract : The most severe consequences of drug abuse include infectious diseases, overdoses, and drug‐related deaths. As the range of toxicologically relevant compounds is continually changing due to the emergence of new psychoactive substances (NPS), laboratories are encountering analytical challenges. Current immunoassays are insufficient for determining the whole range of the drugs abused, and a broad‐spectrum screening method is therefore needed. Here, the patterns of drug abuse in two groups of drug users were studied from urine samples using a comprehensive screening method based on high‐resolution time‐of‐flight mass spectrometry. The two groups comprised drug abusers undergoing opioid maintenance treatment (OMT) or drug withdrawal therapy and routinely visiting a rehabilitation clinic, and drug abusers with irregular attendance at a harm reduction unit (HRU) and suspected of potential NPS abuse. Polydrug abuse was observed in both groups, but was more pronounced among the HRU subjects with a mean number of concurrent drugs per sample of 3.9, whereas among the regularly treated subjects the corresponding number was 2.1. NPS and pregabalin were more frequent among HRU subjects, and their abuse was always related to drug co‐use. The most common drug combination for an HRU subject included amphetamine, cannabis, buprenorphine, benzodiazepine, and alpha‐pyrrolidinovalerophenone. A typical set of drugs for treated subjects was buprenorphine, benzodiazepine, and occasionally amphetamine. Abuse of several concurrent drugs poses a higher risk of drug intoxication and a threat of premature termination of OMT. Since the subjects attending treatment used fewer concurrent drugs, this treatment could be valuable in reducing polydrug abuse. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Comprehensive UHPLC‐HR‐TOF‐MS based confirmation level screening was employed to determine the accurate drug abuse patterns of drug users with different attendance for drug treatment. Those subjects regularly attending treatment mainly abused medicinal buprenorphine and benzodiazepines. Conversely, the conventional illicit drugs amphetamine and cannabis were more frequent among the subjects irregularly attending treatment, together with a higher rate of new psychoactive substances and polydrug abuse. Treatment of drug abusers thus could be valuable in reducing polydrug abuse.